Histological features of sclerosing cholangitis in patients with chronic ulcerative colitis. Issue 7 (July 1985) - Barbatis, C; Grases, P; Shepherd, H A; Chapman, R W; Trowell, J; Jewell, D P; McGee, J O
Abstract : Primary sclerosing cholangitis was diagnosed radiologically in 16 of 681 patients (2.2%) with chronic ulcerative colitis in a follow up study at the gastroenterology unit in Oxford. On the basis of established histological criteria, the liver biopsy was considered diagnostic in only half of the cases. The histological findings in these cases were therefore reassessed to determine whether the accuracy of biopsy diagnosis could be improved. The most common specific histological feature was periductal concentric fibrosis of small interlobular bile ducts, even in the absence of inflammation. Other common features were bile ductular proliferation associated with diminution or absence of interlobular bile ducts. Degeneration of bile duct epithelium and diffuse infiltration of portal tracts by mononuclear cells and polymorphonuclear leucocytes were accompanying features. Piecemeal necrosis without rosette formation was found in about half the biopsies. When all these features were considered together a biopsy diagnosis of primary sclerosing cholangitis was established in 14 of 16 cases.